Getting Out the Vote With Evaluative Thinking. (September 2015) - Bhatti, Yosef; Dahlgaard, Jens Olav; Hansen, Jonas H.; Hansen, Kasper M.
Democratic institutions often do not evaluate their instruments. By working closely with authorities, we developed a field experiment to examine an initiative to increase voter turnout among 18-year-olds that had not previously been evaluated. Particular attention was paid to developing an appropriate program theory and to designing the evaluation in a manner that was consistent with legal and ethical requirements. The program distributed different versions of mobilization letters to the newly enfranchised voters. The treatment effect was positive on turnout and diminished the gap in turnout across population groups, and the effects of the treatments were strongest for individuals with the lowest initial propensity to vote. Cost-effectiveness analysis indicated that the price of an additional vote was approximately USD$136. Our findings influenced policy design and helped establish the principle of evaluative thinking as an integrated part of the future program.